Factors affecting behaviors during complementary feeding in infants and children aged 6–24 months - Yagmur Demirel Ozbek; Isa Celik; Aysenur Sahin Bilgin (PLoS ONE, 2025)
The process that begins around the 6th month of life and continues until the 24th month is called the complementary feeding period. During this period, infants and children start receiving foods that complement breast milk or formula for the first time. The psychosocial factors the infants and children encounter during this period may affect their growth and health in later life. This cross-sectional and descriptive study aimed to examine the factors influencing behaviors of infants and children during complementary feeding. The study sample included 345 mothers with infants and children aged 6–24 months. The research data were collected using two forms and one scale. The first form contained questions about the mothers’ sociodemographic characteristics, sources of support in childcare, and information sources related to complementary feeding. The second form contained questions about the sociodemographic characteristics of infants and children, the presence of allergies, breastfeeding, and feeding status. The scale used was the validated Behaviors of Transition to Complementary Feeding Scale. The effect of independent variables on behavior of infants and children during complementary feeding was examined using multiple linear regression analysis. Infants/children older than 12 months exhibited more negative behaviors during complementary feeding compared with those aged 6–12 months. The study also found that being the first infant/child in the family had a negative impact on behaviors during complementary feeding. Infants and children currently receiving only complementary feeding displayed more positive behaviors during the complementary feeding process. Paternal support in childcare positively influenced behaviors during this period. In conclusion, complementary feeding is a multifaceted process influenced by various factors, including the infant’s and child’s age, family dynamics, and parental support. Strategies to support mothers, involve fathers, and provide reliable information can facilitate a smoother process of complementary feeding and promote healthier feeding behaviors in infants and children. Descriptive, interventional, qualitative, and mixed-methods studies are required to analyze these factors in detail and improve the complementary feeding process.